2021
DOI: 10.1186/s41983-021-00360-x
|View full text |Cite
|
Sign up to set email alerts
|

Role of contrast-enhanced FLAIR MRI in diagnosis of intracranial lesions

Abstract: Background MR imaging plays a significant role in detection and characterization of different brain diseases. The role of the post-contrast T1-weighted image magnetic resonance imaging (T1W MRI) sequence has been widely established in previous studies and clinical practice. In this study, we aim to share our experience as regards the added value of contrast-enhanced fluid-attenuated inversion recovery (CE-FLAIR) sequence in the diagnosis of various intracranial pathological conditions and evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
2
2
0
Order By: Relevance
“…Our results showed significantly higher lesion SI on CE-FLAIR images compared to pre contrast ones and this proved the presence of lesion enhancement on CE-FLAIR images, for observer one, the mean CEI was 88 ranging from 0.5 to 651, for observer two, the mean CEI was 83 ranging from 0.5 to 651 (ICC = 0.959, 95% CI 0.933-0.975). These results were in line with another study [19] which found higher CEI in CE-FLAIR in comparison with pre-contrast FLAIR images with CEI ~ 262 ranging from 40 up to 1708.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results showed significantly higher lesion SI on CE-FLAIR images compared to pre contrast ones and this proved the presence of lesion enhancement on CE-FLAIR images, for observer one, the mean CEI was 88 ranging from 0.5 to 651, for observer two, the mean CEI was 83 ranging from 0.5 to 651 (ICC = 0.959, 95% CI 0.933-0.975). These results were in line with another study [19] which found higher CEI in CE-FLAIR in comparison with pre-contrast FLAIR images with CEI ~ 262 ranging from 40 up to 1708.…”
Section: Discussionsupporting
confidence: 92%
“…The higher contrast to background ratio on CE-FLAIR can be explained by higher inherent soft tissue contrast resolution in FLAIR compared to T1W sequence. These results were supported by the results of study conducted by Mustafa et al [19] who found higher contrast to background ratio in CE-FLAIR than in CE-T1WI. They found the contrast to background enhancement ratio ranging from 0.2 to 3 in CE-FLAIR compared to 0.05 to 1.2 in CE-T1WI.…”
Section: Discussionsupporting
confidence: 86%
“…For primary non-gestational mediastinal choriocarcinoma, the diagnosis relies on radiological examinations followed by biopsy and histochemical staining 8. In patients with intra-axial brain lesions, contrast-enhanced brain MRI FLAIR images provide better neuroradiological anatomic descriptions 25 26. In our case, the enhancement of the intra-axial midbrain lesion was more conspicuous using this sequence.…”
Section: Discussionmentioning
confidence: 76%
“…In T1-weighted sequences (T1w), contrast-enhancing components can quantify the disruption volume of the blood-brain barrier (BBB), allowing for the detection of malignant tumors. T2-FLAIR-weighted images demonstrate abnormalities resulting from a combination of non-enhancing tumors, subfocal edema, and treatment-related changes (gliosis, leukoencephalopathy, and necrosis) [22,23]. Despite this, this technique has several limitations.…”
Section: Magnetic Resonance Imaging (Mri)mentioning
confidence: 99%